2008
DOI: 10.1371/journal.pone.0003149
|View full text |Cite|
|
Sign up to set email alerts
|

A β-Lactam Antibiotic Dampens Excitotoxic Inflammatory CNS Damage in a Mouse Model of Multiple Sclerosis

Abstract: In multiple sclerosis (MS) and its animal model experimental autoimmune encephalomyelitis (EAE), impairment of glial “Excitatory Amino Acid Transporters” (EAATs) together with an excess glutamate-release by invading immune cells causes excitotoxic damage of the central nervous system (CNS). In order to identify pathways to dampen excitotoxic inflammatory CNS damage, we assessed the effects of a β-lactam antibiotic, ceftriaxone, reported to enhance expression of glial EAAT2, in “Myelin Oligodendrocyte Glycoprot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 52 publications
2
68
0
Order By: Relevance
“…EAAT2 upregulation, we note that not all studies have confirmed that EAAT2 can be upregulated by ceftriaxone (39,40). Similarly, our study found only marginal upregulation of EAAT2 with ceftriaxone administration to mice ( Figure 3F).…”
Section: Methodssupporting
confidence: 59%
“…EAAT2 upregulation, we note that not all studies have confirmed that EAAT2 can be upregulated by ceftriaxone (39,40). Similarly, our study found only marginal upregulation of EAAT2 with ceftriaxone administration to mice ( Figure 3F).…”
Section: Methodssupporting
confidence: 59%
“…Transport currents that are due to electrogenic glutamate transport were therefore determined by subtracting whole-cell currents before application of 0.5 mM L-glutamate from currents measured in the same cell after substrate application (Fig. 1B, inset) (5,34,35). These current components required internal K ϩ (12) and were blocked by external TBOA (data not shown).…”
Section: C-terminal Truncations Affect Eaat2-mediated Glutamatementioning
confidence: 99%
“…For functional analysis, dentritic cells (DCs) from wt or Stim2 2/2 mice were prepared from BM cells flushed from femur and tibia bones as described before (19). BM-derived DCs were harvested on day 8, and 2 3 10 6 cells in 1 ml splenocyte complete medium were incubated with 50 mg/ml MOG 35-55 for 6 h. Thereafter MOG 35-55 -loaded DCs (1 3 10 5 ) were cocultured with MACS isolated CD4 + T cells (5 3 10 5 ) (Miltenyi Biotec, Bergisch Gladbach, Germany) for 3 d, and supernatants were assessed for IFN-g and IL-17 levels by ELISA.…”
Section: Immunotyping and Analysis Of Ag Presentationmentioning
confidence: 99%